2010
DOI: 10.34194/geusb.v22.4733
|View full text |Cite
|
Sign up to set email alerts
|

Lithostratigraphy of the Upper Oligocene – Miocene succession of Denmark

Abstract: This paper presents a revised lithostratigraphic scheme for the uppermost Upper Oligocene – Miocene succession of Denmark. The marine Oligocene Brejning Clay Member is upgraded to formation status and includes the Sydklint Member and the Øksenrade Member (new). The shallow marine and deltaic deposits of mainly Early Miocene age are included in the Ribe Group (new) while the fully marine Middle and Upper Miocene clay-rich deposits are referred to the Måde Group (new). The Ribe Group is subdivided into 6 formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 57 publications
1
31
0
Order By: Relevance
“…The relative shallow depositional environment of the Genk Member despite the deposition during a eustatic sealevel rise related to the middle Miocene Climatic Optimum (MMCO, 17-14.5 Ma) (Zachos et al, 2001;Miller et al, 2005;), can be explained by an increase in sediment supply . A similar explanation was given for the synchronous (Langhian) shallowing in the eastern North Sea Basin (Rasmussen et al, 2010).…”
Section: Depositional Environment Of the Berchem And Bolderberg Formasupporting
confidence: 60%
See 2 more Smart Citations
“…The relative shallow depositional environment of the Genk Member despite the deposition during a eustatic sealevel rise related to the middle Miocene Climatic Optimum (MMCO, 17-14.5 Ma) (Zachos et al, 2001;Miller et al, 2005;), can be explained by an increase in sediment supply . A similar explanation was given for the synchronous (Langhian) shallowing in the eastern North Sea Basin (Rasmussen et al, 2010).…”
Section: Depositional Environment Of the Berchem And Bolderberg Formasupporting
confidence: 60%
“…The latter authors' dinocysts species analyses indicated a middle to early late Serravallian age for the maximum flooding surface. Also, in other parts of the North Sea Basin, such as the southern Roer Valley Graben or eastern North Sea Basin, indications for Serravallian transgression were found despite eustatic sea-level lowering (Rasmussen et al, 2010;Thöle et al, 2014;Prinz et al, 2017). Rasmussen (2004a) explained the relative sea-level rise during eustatic sea-level lowering by Serravallian tectonic subsidence of the North Sea Basin.…”
Section: Depositional Environment Of the Berchem And Bolderberg Formamentioning
confidence: 96%
See 1 more Smart Citation
“…Consequently, most of the present-day Denmark became land during the early Miocene (Fig. 1; Rasmussen et al 2010). Major reorganisation of the tectonic regime during the mid-Miocene resulted in flooding of the early Miocene deltas in the North Sea, and marine conditions were re-established.…”
Section: Geological Settingmentioning
confidence: 99%
“…Detailed studies of outcrops, drilling and analysis of more than 50 boreholes, acquisition of high-resolution seismic data and the development of a solid biostratigraphic framework for the succession now exist (e.g. Dybkjaer & Rasmussen 2000, 2007Rasmussen et al 2010).…”
Section: Introductionmentioning
confidence: 99%